After Steve : how Apple became a trillion-dollar company and lost its soul - Mickle, Tripp (William Morrow, an imprint of HarperCollinsPublishers, 2022)
Examines the path of Apple after the death of Steve Jobs and how the selection of Tim Cook as his successor led to the prioritization of revenue growth over innovation.